2020
DOI: 10.1016/j.ridd.2019.103570
|View full text |Cite
|
Sign up to set email alerts
|

Combined action observation and motor imagery facilitates visuomotor adaptation in children with developmental coordination disorder

Abstract: Greg (2020) Combined action observation and motor imagery facilitates visuomotor adaptation in children with Developmental Coordination Disorder. Research in Developmental Disabilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 65 publications
4
51
0
Order By: Relevance
“…Recent work by Scott et al 22 and Marshall et al 23 provided further empirical support for the improved efficacy of the combined use of motor imagery and action observation over and above the isolated use of either motor imagery or action observation. Marshallet al, 23 for example, tested the combined use of motor imagery and action observation to examine its effect on the kinematics of eye–hand coordination during a visuomotor rotation task. The results showed that motor performance improved in children with DCD, which, according to the authors, provides further support for the internal modeling deficit hypothesis.…”
Section: The Use Of Motor Imagery and Action Observation For Remediatmentioning
confidence: 97%
See 1 more Smart Citation
“…Recent work by Scott et al 22 and Marshall et al 23 provided further empirical support for the improved efficacy of the combined use of motor imagery and action observation over and above the isolated use of either motor imagery or action observation. Marshallet al, 23 for example, tested the combined use of motor imagery and action observation to examine its effect on the kinematics of eye–hand coordination during a visuomotor rotation task. The results showed that motor performance improved in children with DCD, which, according to the authors, provides further support for the internal modeling deficit hypothesis.…”
Section: The Use Of Motor Imagery and Action Observation For Remediatmentioning
confidence: 97%
“…That is, in line with the model, the combined use of motor imagery and action observation was a more effective tool for impacting motor skills in children with varying motor abilities compared with motor imagery and action observation in isolation. Recent work by Scott et al 22 and Marshall et al 23 provided further empirical support for the improved efficacy of the combined use of motor imagery and action observation over and above the isolated use of either motor imagery or action observation. Marshallet al, 23 for example, tested the combined use of motor imagery and action observation to examine its effect on the kinematics of eye–hand coordination during a visuomotor rotation task.…”
Section: The Use Of Motor Imagery and Action Observation For Remediatmentioning
confidence: 97%
“…Further studies, with a larger sample size, are needed, to further explore this area. Different studies have highlighted the importance of AO and MI for rehabilitation regimes, and its fundamental role in neurological conditions (Abbruzzese et al 2015;Marshall et al 2020;Mulder 2007) and immobilization (Bassolino et al 2014). Under the right conditions, sonification could represent important strategy to maximize learning in clinical conditions, such as stroke survivors (Scholz et al 2014(Scholz et al , 2015(Scholz et al , 2016, but could also be a viable sensory substitution strategy for conditions such as deafferentation (Danna and Velay 2017;Danna et al 2015).…”
Section: Combined Action Observation and Motor Imagery Training And Ementioning
confidence: 99%
“…Under the right conditions, sonification could represent important strategy to maximize learning in clinical conditions, such as stroke survivors (Scholz et al 2014(Scholz et al , 2015(Scholz et al , 2016, but could also be a viable sensory substitution strategy for conditions such as deafferentation (Danna and Velay 2017;Danna et al 2015). Lastly, further development of sonification research may find application in the field of brain-computer interfaces, by affording strategies to improve embodiment of non-body objects, such as neuroprostheses (D'Alonzo et al 2019;Di Pino et al 2014a, b, 2020, an issue that crucial for optimal development of the field (Makin et al 2017).…”
Section: Combined Action Observation and Motor Imagery Training And Ementioning
confidence: 99%
“…Within the task-oriented approach, imagery trainings (alone or in combination with observational interventions) also seem to be promising. For instance, Marshall et al. (2020) showed the effectiveness of an intervention based on the observation of videos showing the performance of some motor tasks accompanied by concurrent motor imagination (mental rehearsal) of that action for the empowerment of eye-hand coordination in 7–11 year-old children with DCD.…”
Section: Testing Motor Functioning and Treating School-aged Pupils Wimentioning
confidence: 99%